Hybrid-Filler and Structural Strategies for Self-Lubricating Epoxy Composites and Coatings: A Focused Review - Yang, Guangya (International Journal of Mechanical and Electrical Engineering, 2025)
Self-lubricating epoxy (EP) composites and coatings are required in bearings, gears, and structural tribo-components that must operate with low friction and stable wear across dry, boundary, mixed, and corrosion-coupled environments. The uploaded literature converges on three synergistic strategies: solid-lubricant nanofillers and hybrids (graphite/graphene/GO, h-BN, MXene, ZnS–GO) that form robust transfer films and provide thermal/electrical pathways; encapsulated and vascular lubrication that releases liquids on demand; and fiber/architected reinforcements (carbon fabrics, filament winding, substrate engineering) that deliver load-bearing capacity and anisotropic transport. This review synthesizes mechanisms and trends strictly from the uploaded sources, embeds research-style tables summarizing systems, processes, test contexts, and outcomes, and discusses open issues around dispersion and interfacial bonding, film stability under heat and shear, corrosion–tribology coupling, dosing/triggering in on-demand lubrication, test comparability, and manufacturing scale-up. We conclude with future directions emphasizing multi-scale hybridization, adaptive lubrication networks (capsule+vascular), thermal/anti-corrosion co-design, oriented architectures, and application-driven substrate/process choices for water-lubricated and oscillatory bearings.